2018
DOI: 10.1103/physrevb.98.121113
|View full text |Cite
|
Sign up to set email alerts
|

Revising the 4f symmetry in CeCu2Ge2 : Soft x-ray absorption and hard x-ray photoemission spectroscopy

Abstract: We present a detailed study on the 4f ground-state symmetry of the pressure-induced superconductor CeCu 2 Ge 2 probed by soft x-ray absorption and hard x-ray photoemission spectroscopy. The revised Ce 4f ground states are determined as | 7 = √ 0.45 |J z = ± 5 2 − √ 0.55 |∓ 3 2 with-type in-plane rotational symmetry. This gives an in-plane magnetic moment consistent with the antiferromagnetic moment as reported in neutron measurements. Since the in-plane symmetry is the same as that for the superconductor CeCu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…We further assume that the l c → l c + 1 transitions are predominant over the l c → l c − 1 transitions 25,39 , and therefore the interference effects between the outgoing l c + 1 and l c − 1 photoelectron waves are negligible 40 . Indeed, with this assumption, the experimental polarizationdependent angle-resolved core-level photoemission spectra have been well reproduced by spectral simulations [20][21][22][23] . By substituting Eq.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…We further assume that the l c → l c + 1 transitions are predominant over the l c → l c − 1 transitions 25,39 , and therefore the interference effects between the outgoing l c + 1 and l c − 1 photoelectron waves are negligible 40 . Indeed, with this assumption, the experimental polarizationdependent angle-resolved core-level photoemission spectra have been well reproduced by spectral simulations [20][21][22][23] . By substituting Eq.…”
mentioning
confidence: 65%
“…Recently, it has been reported that the ground-state 4f -orbital symmetry can be uniquely determined by linear polarization-dependent angle-resolved core-level photoemission of strongly correlated rare-earth compounds not only in tetragonal symmetry 20,21 but also in cubic symmetry 22,23 . This technique is promising for revealing the ground-and excited-state orbital symmetry of strongly correlated electron systems, as it is complemen-tary to LD-XAS and LD-NIXS.…”
mentioning
confidence: 99%
“…The vertical bars are guide to the eye. (c) Spectral simulations based on the Ce 3+ ionic model assuming the Γ 6 symmetry and the Γ 7 symmetry with α 2 = 0.45 [16].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, it is difficult to detect experimentally the anisotropic 4 f charge distributions in cubic symmetry. Recently, the linear dichroism (LD) in hard X-ray photoemission spectroscopy (HAXPES) has been reported as a powerful method for revealing the 4 f CEF ground state of such strongly correlated electron systems [6][7][8][9][10][11]. In this paper, we demonstrate that the linear dichroism in corelevel photoemission spectroscopy can reveal not only the CEF ground state but also the excited state in cubic Pr compounds by the temperature dependence of LD in core-level photoemission of cubic PrBe 13 .…”
Section: Introductionmentioning
confidence: 99%